2014
DOI: 10.1007/s10295-013-1350-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of genes involved in initial xylose metabolism and the oxidative pentose phosphate pathway in the improved xylose-utilizing Saccharomyces cerevisiae through evolutionary engineering

Abstract: Fermentation of xylose in lignocellulosic hydrolysates by Saccharomyces cerevisiae has been achieved through heterologous expression of the xylose reductase (XR)-xylitol dehydrogenase (XDH) pathway. However, the fermentation efficiency is far from the requirement for industrial application due to high yield of the byproduct xylitol, low ethanol yield, and low xylose consumption rate. Through evolutionary engineering, an improved xylose-utilizing strain SyBE005 was obtained with 78.3 % lower xylitol production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 64 publications
1
36
0
Order By: Relevance
“…Further mutagenesis of the Y353 position showed that other substitutions can result in improved growth, but the original cysteine mutant appears to exhibit the strongest phenotype. A previous study also described a point mutation in CYC8 in an evolutionary engineering experiment which optimized D-xylose consumption in a D-xylose-fermenting S. cerevisiae strain (26). Either because of that mutation or because of two other mutations found in the evolved strain (26), the expression levels of the genes involved in xylose metabolism (e.g., XYL1 and XYL2) were increased, causing improved D-xylose consumption but not increased growth on D-xylose in the presence of D-glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Further mutagenesis of the Y353 position showed that other substitutions can result in improved growth, but the original cysteine mutant appears to exhibit the strongest phenotype. A previous study also described a point mutation in CYC8 in an evolutionary engineering experiment which optimized D-xylose consumption in a D-xylose-fermenting S. cerevisiae strain (26). Either because of that mutation or because of two other mutations found in the evolved strain (26), the expression levels of the genes involved in xylose metabolism (e.g., XYL1 and XYL2) were increased, causing improved D-xylose consumption but not increased growth on D-xylose in the presence of D-glucose.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of glucose consumption in SyBE_Sc122001 was due to the increase of metabolic flux into the PP pathway from glucose, which drove the increase in xylose consumption due to the coupling by RPE1 deletion. Besides, ZWF1 overexpression also offered more NADPH as the co-factor for xylose reductase to accelerate xylose utilization [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…6634), we named as E7. (Zha et al 2014). The mating selection medium (YNBX) contained 6.7 g/L yeast nitrogen base (YNB), 20 g/L xylose, 20 g/L agar, and 20 g/L of xylose.…”
Section: Materials and Strainsmentioning
confidence: 99%
“…Recently, engineered strains for efficient xylose utilization, by introducing a xylose pathway, has attracted extensive attention. A xylose fermenting yeast, which expresses the xylose reductase (XR) and a NADP+-preferring xylitol dehydrogenase (XDH) mutant, was genetically constructed (Zha et al 2014). Then an adapted strain (E7) with improved xylose fermentation capability (S. cerevisiae CGMCC NO.…”
Section: Introductionmentioning
confidence: 99%